Measuring the dynamics of remembered experience over time - Karapanos, Evangelos; Zimmerman, John; Forlizzi, Jodi; Martens, Jean-Bernard (My University, 2010)
A wealth of studies in the field of user experience have tried to conceptualize new measures of product quality and inquire into how the overall goodness of a product is formed on the basis of product quality perceptions. An interesting question relates to how the perception as well as the relative dominance of different product qualities evolve across different phases in the adoption of a product. However, temporality of experience poses substantial challenges to traditional reductive evaluation approaches. In this paper we present an alternative methodological approach for studying how users' experiences with interactive products develop over time. The approach lies in the elicitation of rich qualitative insights in the form of experience narratives, combined with content-analytical approaches for the aggregation of idiosyncratic insights into generalized knowledge. We describe a tool designed for eliciting rich experience narratives retrospectively, and illustrate this tool by means of a study that inquired into how users' experiences with mobile phones change over the first 6 months of use. We use the insights of the study to validate and extend a framework of temporality proposed by Karapanos et al. (2009b).
Keywords: User experience; Experience-centered design; Qualitative methods; Longitudinal methodology